BLENDED LEARNING AS A METHOD FOR IMPROVING STUDENTS’ ACHIEVEMENT IN DERMATOTHERAPY: A PRELIMINARY STUDY - Sri Linuwih Menaldi; Hanny Nilasari; Githa Rahmayunita; Siti Farida; Nanda L. Prasetya (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Dermatotherapy is an important topic in Dermatology and Venereology module. The time allocated for dermatotherapy topic is limited, so that the development of learning method is needed to achieve the learning objectives. Blended learning is a combination of e-learning and face to face lecture session. This method is often used when there is less time available for lecturing and limited number of teachers. This learning method is expected to be more effective and efficient for the students and also the teachers. This study was conducted to examine the effectiveness of blended learning method used in dermatotherapy topic, and to identify the obstacle of using this method. Methods: This study is a cross sectional study, using quantitative and qualitative approach, involving 22 fifth-year medical students of Faculty of Medicine Universitas Indonesia who enrolled in dermatology and venereology module. We collected data from questionnaire, pre and post-test, and feedback from the students. Comparison of pre-test and post-test results were analysed using paired T test, and followed by bivariate test of students’ characteristic, gadget usage and e-learning activities associated with the increased post-test score.Results: An increased in post-test score was found to be statistically significant (p<0.05). Approximately 95,4% of students passed the final exam on the dermatotherapy subject. Bivariate analysis revealed that the number of gadgets owned, digital usage and e- learning activities did not have a significant effect on the post-test score. Based on the students’ feedback, blended learning had a positive impact on helping their learning process; however, the materials of e-learning must be interactive, informative and comprehensive. Face-to-face lecture is still an important component in learning hence it is irreplaceable. Conclusion: Blended learning is an effective method of learning and should be considered if there is limitation of lecture time and number of teachers available. By using this method, medical students are more flexible in their study and it can be adjusted to their own learning style hence heling them understand better. Further development and improvement are needed for this method as to achieve the learning objectives. Keywords: blended learning, dermatotherapy, medical students